CRISPR/Cas9 in Gastrointestinal Malignancies - Jefremow, André; Neurath, Markus F.; Waldner, Maximilian J. (Frontiers in Cell and Developmental Biology, 2021)
Gastrointestinal (GI) cancers such as colorectal cancer (CRC), gastric cancer (GC), esophageal cancer (EG) pancreatic duct adenocarcinoma (PDAC) or hepatocellular cancer (HCC) belong to the most commonly diagnosed types of cancer and are among the most frequent causes of cancer related death worldwide. Most types of GI cancer develop in a stepwise fashion with the occurrence of various driver mutations during tumor progression. Understanding the precise function of mutations driving GI cancer development has been regarded as a prerequisite for an improved clinical management of GI malignancies. During recent years, CRISPR/Cas9 has developed into a powerful tool for genome editing in cancer research by knocking in and knocking out even multiple genes at the same time. Within this review, we discuss recent applications for CRISPR/Cas9-based genome editing in GI cancer research including CRC, GC, EG, PDAC and HCC. These applications include functional studies of candidate genes in cancer cell lines or organoids in vitro as well as in murine cancer models in vivo, library screening for the identification of previously unknown driver mutations and even gene therapy of GI cancers.